Rising to the Occasion: The Importance of the Pandemic for Faculty Adoption Patterns - Jing Zhang; Georgette E. Dumont; Becky G. Sumbera; Pamela Medina; Melika Kordrostami; Anna Y Ni (Online Learning, 2023)
Technology adoption patterns, in general, have been shown to have a common set of predictive factors such as performance expectancy, social influence, voluntariness, effort expectancy, and facilitating conditions. However, the significance of such factors varies dramatically by situation and conditions. In the faculty adoption of online teaching modalities, three conditions were investigated in a university case study with 180 faculty respondents. Using the unified theory of acceptance and use of technology model, participants were asked to respond to questions about these factors prior to the pandemic, their perceptions about continuing pre-pandemic use in the future, and their perceptions about increasing pre-pandemic adoption of online teaching in the future. Critical to prior expectations were performance expectancy and level of effort. Continued use relied on all five factors, but only the negative aspects of social influence were significant. Factors affecting increased adoption (assuming voluntariness) were performance expectancy and facilitating conditions. Findings suggest that increased exposure to online teaching may not be as crucial as the quality of faculty experiences during the pandemic. The rationale for these factor shifts is provided, the effects of institutional support are discussed, the threats and limitations to generalizability are reviewed, and the ramifications for institutions trying to enhance faculty adoption are summarized.